Threatened, host-specific affiliates of a red-listed host: Three new species of Acanthobothrium van Beneden, 1849 (Cestoda: Onchoproteocephalidea) from the endangered white skate, Rostroraja alba (Lacépède). (April 2022) - Van Der Spuy, Linda; Smit, Nico J.; Schaeffner, Bjoern C.
Abstract: The white skate, Rostroraja alba (Lacépède), is listed as an endangered species, the second-highest category before being declared extinct in the wild, in the International Union for Conservation of Nature's (IUCN) Red List of Threatened Species. This species is heavily affected by anthropogenic impacts such as capture induced stress by overfishing and by-catch, habitat degradation and pollution that caused a drastic decline in populations in recent years. As part of a larger study on elasmobranch affiliates in southern Africa, two specimens of R. alba were screened. Three species of the tapeworm genus Acanthobothrium van Beneden, 1849 (Cestoda: Onchoproteocephalidea) were discovered. Application of Ghoshroy and Caira's classification system facilitated the differentiation of congeners through a combination of specific morphological characteristics. As a consequence, three species new to science are described herein, namely Acanthobothrium umbungus n. sp., Acanthobothrium usengozinius n. sp., and Acanthobothrium ulondolozus n. sp. In light of these new discoveries from an endangered host, it is apparent to address the conservation status of its affiliate species, that co-evolved with their elasmobranch hosts for millions of years, thereby creating unique and intimate host-parasite interrelationships. Currently, altering environmental conditions caused by anthropogenic pressures have direct impacts on this host-parasite system with increasing risks of extinction. As merely 9% of elasmobranchs in South African waters have been examined for endohelminths and other affiliate taxa, extensive studies on these organisms and their hosts implementing multisource approaches are needed. This will provide a better understanding on the intimate nature of host-parasite systems that may lead to new prospects in conservation science and the preservation of threatened host species, such as R. alba, together with their unique fauna of affiliate species. Graphical abstract: Image 1 Highlights: Three new species of Acanthobothrium were discovered in the endangered white skate, Rostroraja alba, off the coast of South Africa. The three species described ( A. umbungus n. sp., A. usengozinius n. sp., and A. ulondolozus n. sp.) display merely a single cestode genus among the hidden diversity of species from elasmobranchs. The current increase in threatened free-living host species results in an even greater loss in affiliate species that remain unknown and scientifically underexplored. Assessing the status and incorporating affiliate species (i.e. cestodes) into novel conservation schemes may contribute to the conservation of threatened host species and marine populations worldwide, which, in turn, will protect affiliate species as vital "key players" for host species and entire ecosystems.